Presleep heart-rate variability biofeedback improves mood and sleep quality in chinese winter olympic bobsleigh athletes - Li, Q.; Steward, C. J.; Cullen, T.; Che, K.; Zhou, Y. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To evaluate the effectiveness of heart-rate variability (HRV) biofeedback in improving autonomic function, mood, and sleep in elite bobsleigh athletes.